Survival rate of dental implants installed by postgraduate students attending an implantology program in Brazil: A 52-month retrospective analysis - Myungjin Kang; Henrique Smanio Neto; André Antonio Pelegrine; Cecilia Pedroso Turssi; Juliana Trindade Clemente-Napimoga; Marcelo Henrique Napimoga (Frontiers in Dental Medicine, 2023)
ObjectivesThe aim of this study was to assess the survival rate and identify possible risk factors for failure of dental implants placed by postgraduate students in Implantology at a Brazilian Dental School.Materials & methodsA retrospective observational study was conducted to evaluate 1,164 dental implants placed by postgraduate students in Implantology at São Leopoldo Mandic Dental School (Brazil) during a 3-year time period (2018–2020). Data collected from the patients' medical charts included the following: implant loss, gender, diabetes, smoking, continuous use of medication, type of implant connection system, implant position (maxilla or mandible), previous bone grafting and type of prosthetic provisioning (temporary prosthesis, immediate prosthesis or permanent prosthesis). The association between all the independent variables and implant loss was run using χ2 and G tests (α = 5%). The implant survival rate was estimated using Kaplan-Meier curve.ResultsGender, diabetes, smoking, continuous use of medication, type of implant connection system, implant position, previous bone grafting and type of prosthetic provisioning showed no statistically significant association with implant loss. Of the 1,164 implants installed, 29 (2.5%) failed. The overall survival rate of dental implants placed by postgraduate students up to 52 months was 90.5% (IC95%: 74.5%–96.7%).ConclusionsImplants placed by postgraduate students in Implantology at São Leopoldo Mandic Dental School showed a high survival rate, with gender, diabetes, smoking, continuous use of medication, type of implant connection system, implant position, previous bone grafting and type of prosthetic provisioning not accounting for the risk of implant failure.